AKTIVITAS EKONOMI DAN KUALITAS RUANG TERBUKA HIJAU AKTIF DI KOTA DENPASAR - Dwipa Tanaya, I Dewa Made (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 1 (2016): April 2016, 2016)
Abstract Active green open space has an important role to play in urban environment. This study looks at functions accommodated by this spatial formation that exist in Kota Denpasar. Since these functions are not planned for in the first instance, informal economic activities act to the detriment of such spaces rather than reinforcing them with planned informal economic activities. Qualitative methods are used in the study. Physical and non- physical elements are identified. The former embrace scale of the park, the type of facilities it offers, the quality of design and other physical conditions. Non-physical elements cover an understanding of the park as a responsive, democratic, meaningful and accessible spatial form within our urban environment. Thorough planning is required if economic activities are to be managed and their impacts anticipated. At the same time, any plan must include public education to raise awareness that the quality of the environment is not the responsibility of others but the duty of everybody. The study concludes that economic activities currently bring negative impacts on the quality of the green open space due to a greater consideration by government in the planning stages. Keywords: Open green space, economic activities, impact, open green space quality Abstrak Ruang terbuka hijau aktif memiliki peran penting dalam lingkungan perkotaan. Studi ini bertujuan untuk melihat aktivitas ekonomi yang diwadahi oleh RTH di Kota Denpasar serta menganalisis dan mengkaji bagaimana pemanfaatan ruang untuk aktivitas ekonomi yang ada berdampak terhadap kualitas RTH aktif di Kota Denpasar. Kualitas RTH ditentukan oleh aspek fisik dan non fisik. Aspek fisik mengkaji skala, kelengkapan sarana elemen pendukung, desain, dan kondisi fisik. Aspek non fisik mengkaji masing-masing yang mendemonstrasikan hal responsif, demokratis, memberikan arti dan aksesibilitas . Aktivitas ekonomi memberi pengaruh negatif terhadap kualitas ruang terbuka hijau aktif. Penataan ruang terhadap aktivitas ekonomi bisa dijadikan alternatif untuk mengurangi dampak negatif terhadap kualitas kawasan. Pembelajaran terhadap masyarakat tentang pentingnya menjaga kebersihan lingkungan juga sangat penting untuk dilakukan. Kata kunci: ruang terbuka hijau, aktivitas ekonomi, dampak, kualitas ruang terbuka hijau
Keywords: ruang terbuka hijau, aktivitas ekonomi, dampak, kualitas ruang terbuka hijau